The Role of the Government and Tourists’ Perceptions of Sports Tourism at Belanting River Tubing, Ogan Komering Ulu - Ani, Delta Pitri; Handayani, Widya; Manullang, Jujur Gunawan (PPSDP International Journal of Education, 2024)
This study investigates the critical roles of government actions and tourists’ perceptions in shaping the development and sustainability of sports tourism at Belanting River Tubing in Ogan Komering Ulu, South Sumatra, Indonesia. Employing a qualitative research methodology, data were gathered through semi-structured interviews, focus groups, and field observations, revealing several significant issues. The findings underscore considerable infrastructural deficiencies, including poor road conditions and inadequate facilities hindering the overall tourist experience. Despite various government initiatives promoting the destination, there remains a noticeable gap between planning and practical implementation, causing frustration among local stakeholders. Safety concerns, such as the absence of adequately trained guides and insufficient emergency protocols, further detract from the destination’s attractiveness. The current promotional strategies need to be improved, with many tourists only learning about the site through word-of-mouth rather than practical marketing efforts. At the same time, visitors’ express appreciation for the natural beauty and adventurous opportunities that the challenges above overshadow. Balancing River Tubing offers these positive aspects. The study highlights the necessity of increased community involvement for sustainable tourism development, noting that residents require more training and support. It concludes with recommendations to enhance infrastructure, improve safety measures, strengthen promotional activities, and foster community engagement to ensure the long-term sustainability and success of sports tourism at Belanting River Tubing.